Chemical Vapor Deposition - Recent Advances and Applications in Optical, Solar Cells and Solid State Devices 2016
DOI: 10.5772/63344
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature PureB CVD Technology for CMOS Compatible Photodetectors

Abstract: In this chapter, a new technology for low-temperature (LT, 400°C) boron deposition is developed, which provides a smooth, uniform, closed LT boron layer. This technology is successfully employed to create near-ideal LT PureB (pure boron) diodes with low, deep junction-like saturation currents, allowing full integration of LT PureB photodiodes with electronic interface circuits and other sensors on a single chip. In this way, smart-sensor systems or even charge-coupled device (CCD) or complementary metal oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The idea of the delta-doped p + layer playing any significant role in the junction formation was completely abandoned when it was demonstrated that similar excellent electrical properties could be achieved by boron CVD on n-type crystalline silicon substrates at temperatures as low as 400 • C, at which no doping of boron in silicon is expected [7].…”
Section: Introduction: Initiation and History Of Boron-silicon Junctions And Importance Of Si-based Junctions/diodes In Microelectronicsmentioning
confidence: 99%
“…The idea of the delta-doped p + layer playing any significant role in the junction formation was completely abandoned when it was demonstrated that similar excellent electrical properties could be achieved by boron CVD on n-type crystalline silicon substrates at temperatures as low as 400 • C, at which no doping of boron in silicon is expected [7].…”
Section: Introduction: Initiation and History Of Boron-silicon Junctions And Importance Of Si-based Junctions/diodes In Microelectronicsmentioning
confidence: 99%